KRAS and NRAS mutational gene profile of metastatic colorectal cancer patients in Jordan - Awidi, Muhammad (PLoS One, 2019)
BACKGROUND: A constitutively active RAS protein in the absence of stimulation of the epidermal growth factor receptor (EGFR) is the result of mutations in KRAS and NRAS genes. Mutations in the KRAS exon 2 and outside exon 2 have been found to predict the resistance to anti-EGFR monoclonal therapy. A substantial proportion of metastatic colorectal cancer cases (mCRC) exhibit RAS mutations outside KRAS exon 2, particularly in KRAS exon 3 and 4 and NRAS exons 2 and 3. No data about RAS mutations outside KRAS exon 2 are available for Jordanian patients with mCRC. We aim to study the molecular spectrum, frequency, and distribution pattern of KRAS and NRAS mutations in Jordanian patients with mCRC. METHODS: A cohort of 190 Jordanian metastatic colorectal cancer patients were enrolled in the trial. We detected mutations in exon 2 of the KRAS and NRAS gene as well as mutations outside of exon 2 using the StripAssay technique. The KRAS StripAssay covered 29 mutations and 22 NRAS mutations. RESULTS: Mutations were observed in 92 (48.42%) cases, and KRAS exon 2 mutations accounted for 76 cases (83.69%). KRAS G12D was the most common mutation, occurring in 18 cases, followed by KRAS G12A in 16 cases, and G12T in 13 cases. Mutations outside of KRAS exon 2 represented 16.3% of the mutated cases. Among those, 6 cases (6.48%) carried mutations in NRAS exon 2 and 3, and 10 cases (10.87%) in KRAS exon 3 and 4. CONCLUSION: The frequency of NRAS and KRAS mutations outside of exon 2 appears to be higher in Jordanian patients in comparison with patients from western countries. KRAS mutations outside of exon 2 should be tested routinely to identify patients who should not be treated with anti-EGFR antibodies.